Analisis Kesulitan Belajar Bahasa Arab: Studi Kasus Pada Mahasiswa Semester IV Program Studi PAI IAIN Parepare - Latief, Abdul (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
Arabic is a language rich in rules, structures, and vocabulary. It is also one of the oldest languages in the world. As Muslims, we are obligated to understand Arabic. The Quran, the guide to life for Muslims, was revealed in Arabic. It is impossible for us to understand the Quran without mastering Arabic. This study aims to identify various difficulties in learning Arabic among fourth-semester students of the Islamic Religious Education (PAI) Study Program at IAIN Parepare. These difficulties will be analyzed and then solutions will be proposed. This is a qualitative study using data collection techniques such as observation, interviews, and documentation. Data analysis was conducted using inductive and deductive methods, giving meaning to the collected data, and then drawing conclusions. The results of this study indicate that: 1) Factors contributing to difficulties in learning Arabic among fourth-semester students of the Islamic Religious Education (PAI) Study Program at IAIN Parepare include educators, students, educational background, limited vocabulary, methods, media, time, facilities, environment, physiological factors, and psychological factors. 2) Efforts to overcome difficulties in learning Arabic in the PAI Study Program at IAIN Parepare include Arabic language tutoring, attracting student interest, providing attention, creating a pleasant atmosphere, providing adequate facilities and infrastructure, practicing Arabic language courses, holding learning activities and creating Arabic language study groups